2008
DOI: 10.1016/j.biomaterials.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Size, charge and concentration dependent uptake of iron oxide particles by non-phagocytic cells

Abstract: A promising new direction for contrast-enhanced magnetic resonance (MR) imaging involves tracking the migration and biodistribution of superparamagnetic iron oxide (SPIO)-labeled cells in vivo. Despite the large number of cell labeling studies that have been performed with SPIO particles of differing size and surface charge, it remains unclear which SPIO configuration provides optimal contrast in non-phagocytic cells. This is largely because contradictory findings have stemmed from the variability and imprecis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
256
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(272 citation statements)
references
References 46 publications
13
256
3
Order By: Relevance
“…The study of Thorek and Tsourkas [54] with dextran-iron oxide nanoparticles of different diameters has shown that these were fully soluble at physiological conditions and efficiently internalized up to a size of 100 nm. For all dimensions, the saturating level was reached at a cellular iron concentration below 50 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Thorek and Tsourkas [54] with dextran-iron oxide nanoparticles of different diameters has shown that these were fully soluble at physiological conditions and efficiently internalized up to a size of 100 nm. For all dimensions, the saturating level was reached at a cellular iron concentration below 50 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration and the charge play a significant role in the cellular internalization [25]. For instance, negatively charged fluorescently labeled SPIONs have a higher internalization in prostate-cancer PC-3 cell line as observed via confocal microscopy or flow cytometry, in comparison to positively charged SPIONs [26].…”
Section: Cellular Uptake and Biodistribution Of Superparamagnetic Iromentioning
confidence: 99%
“…The exact mechanism of the biotoxicity of nanosized iron oxides is an ongoing discussion; the most likely causes include size, concentration, and chemical surface modification, as well as incubation time [39]. Voinov et al [40] reported that γ-Fe 2 O 3 nanoparticles 20-40 nm in diameter could mediate the production of highly reactive hydroxyl radicals because an increase in the intracellular free iron level affected the normal ROS-antioxidant balance by promoting ROS production.…”
Section: Articlesmentioning
confidence: 99%